Influence of tumor necrosis factor α inhibitors on testicular function and semen in spondyloarthritis patients - Ramonda, Roberta; Foresta, Carlo; Ortolan, Augusta; Bertoldo, Alessandro; Oliviero, Francesca; Lorenzin, Mariagrazia; Pizzol, Damiano; Punzi, Leonardo; Garolla, Andrea (Fertility and sterility, 2014)
To evaluate sperm parameters and sexual hormones in young males affected with spondyloarthritis (SpA) before and after 1 year of anti-tumor necrosis factor (TNF) α treatment. Prospective case-control study. Rheumatology and human reproduction pathology units at a university hospital. Ten SpA outpatients attending the rheumatology clinic; 20 healthy control subjects attending the unit of human reproduction pathology within an infertility prevention program. At baseline and after a 12-month treatment, disease activity was assessed and an andrologic evaluation made. Rheumatologists assessed anamnestic, clinical, functional, and biomarker data. Andrologists evaluated semen analysis, fluorescence in situ hybridization for chromosomes X, Y, 13, 18, and 21, FSH, LH, and T plasma levels, and testicular color Doppler ultrasound. At baseline, SpA patients showed reduced sperm motility, higher plasma LH and FSH, and lower T levels compared with control subjects; a significant correlation between disease activity and sperm quality was found. After treatment, a statistically significant decrease in sperm aneuploidies and normal hormone levels were observed. Although inflammation in SpA appears to be related to impaired testicular function, anti-TNF-α agents seem to be safe on testicular function and fertility.